Detection of macro-thyrotropinaemia in patients with Hashimotos thyroiditis and subclinical hypothyroidism - E. M. Biktagirova (SPb RAACI, 2020)
The level of thyroid stimulating hormone is one of the diagnostic indicators of thyroid function. In subclinical hypothyroidism, its concentration in the blood serum increases, while the level of thyroid hormones remains normal. One of the reasons for this is the phenomenon of macrotyrotropinemia, in which the macro isoforms of thyrotropin (a complex of thyrotropic hormone with immunoglobulin) are present in the blood. It is assumed that the biological activity of macrotyrotropin is low, and may accumulate in the circulation, causing a falsely elevated level of thyroid-stimulating hormone in serum. The aim of this study is to identify the nature and prevalence of the macrothyrotropinemia phenomenon among patients with subclinical hypothyroidism in presence of autoimmune thyroiditis and a group of healthy donors. Materials and methods: Fifty serum samples of venous blood served as the material for the study: 30 patients with subclinical hypothyroidism in presence of autoimmune thyroiditis; 10, with manifesting hypothyroidism, 10 conditionally healthy donors without thyroid gland pathology (control group). The group was derived from results of the clinical laboratory at the Clinical Hospital at the Kazan station railway. Patients’ blood serum was screened for the presence of macrotrorotropin by polyethylene glycol precipitation method, followed by analysis by gel filtration chromatography. Results of this study were as follows: screening of blood sera was performed by gel filtration and affinity chromatography. Polyethylene glycol was shown to precipitate 50 to 100% serum thyrotropin, of which true macrotrothropin makes 56-98%. In the patients with subclinical hypothyroidism with a thyroid-stimulating hormone level of more than 10 pIU/ml, a trend towards an increase in the level of macrothyrotrophinaemia has been shown. The content of macrotyrotropin complex in patients with subclinical hypothyroidism, in whom the level of antibodies to thyroperoxidase is > 500 U/L, is significantly higher if compared to the patients with manifesting hypothyroidism. Elevated levels of antibodies to thyroperoxidase can lead to the generation of macrotyropin. Our findings have shown that the phenomenon of macrothyrotropinemia is quite common in patients with subclinical and manifesting hypothyroidism with Hashimoto thyroiditis (53.3%) and in control group (25%). Macrotyrotropin complex probably consists of thyrotropin and IgG. Patients with a thyroid-stimulating hormone level of > 10 pIU/ml are candidates for screening for the presence of the macrotyrotropin complex.The activity of the autoimmune process may correlate with the phenomenon of macrothyrotropinemia. The results can be used to develop an additional tool when choosing therapy in clinical practice.